Content design and validation of an instrument to measure safety and health management at work for Colombian organizations - Erazo Imbacuán, Gloria María (Universidad Santo Tomás / Instituto Colombiano de Normas Técnicas y Certificación ICONTEC, 2016)
In Colombia, given the great expectation and evolution of the regulations issued in Law 1562 of 2012 and in Decree 1072 of 2015. For this reason, it is necessary to construct and apply valid and legitimized indicators, since the indicators are the shared vision of the form in That the ends are achieved. This research was designed as an instrument to measure the Safety and Health Management at Work with content validity for Colombian organizations under the high level structure proposed by ISO, which will be the basis of the future ISO 45001. From the review of the literature and the consultation of experts (14 experts from six Occupational Risk Managers) the instrument was built, which integrated and aligned the compliance requirements of Decree 1072 of 2015 and Draft of ISO 45001, Under the principle that the instrument is a tool that provides information for decision making in the prevention and control of risks.